Pengaruh Pembelajaran Prototipe Terhadap Kemandirian Siswa Kelas V UPT SPF SDN 106157 Tahun Ajaran 2022/2023 - Muthalib, Muthalib; Ramadhan, Nuri; Malinda, Leni (Medan Resource Center, 2024)
This research investigates the effect of Prototype Learning (X) on student independence (Y) in class V at UPT SPF SDN 106157 during the 2022/2023 academic year. The study uses an experimental method to analyze the relationship between the Prototype Learning model and students' independence. The results demonstrate that Prototype Learning falls into the